2013
DOI: 10.1111/apm.12159
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between caspofungin or voriconazole and cefoperazone-sulbactam or piperacillin-tazobactam byin vitroandin vivomethods

Abstract: Immunosuppressive patients are at risk of fungal and bacterial infections. Therefore, these patients receive prophylactic, preemptive, empirical or target antifungal and concomitant antibiotic therapy. To this end, caspofungin (CAS) or voriconazole (VRC) antifungals and cefoperazone-sulbactam (CPZ/SAM) or piperacillin-tazobactam (PIP/TAZ) antibiotics may be used. Here, we aimed to investigate the interaction between these antifungals and antibiotics by in vitro and in vivo methods. The interaction was tested b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…albicans . In that study, CPZ/SAM is suggested to have more affinity for the same efflux pump as caspofungin, leading to an increase in intracellular levels of caspofungin and hence, synergy between caspofungin and CPZ/SAM [ 70 ]. In another report, Chen and colleagues demonstrated that posaconazole exhibits synergistic antifungal activity with caspofungin in vitro and in vivo against C .…”
Section: Discussionmentioning
confidence: 99%
“…albicans . In that study, CPZ/SAM is suggested to have more affinity for the same efflux pump as caspofungin, leading to an increase in intracellular levels of caspofungin and hence, synergy between caspofungin and CPZ/SAM [ 70 ]. In another report, Chen and colleagues demonstrated that posaconazole exhibits synergistic antifungal activity with caspofungin in vitro and in vivo against C .…”
Section: Discussionmentioning
confidence: 99%
“…Many animal models have also been used to verify the antifungal activity of antibacterial agents. In the murine model of candidiasis, a combination of cefoperazone–sulbactam, colistin, or meropenem with caspofungin has been found to result in lower fungal burden in the kidneys, than that after treatment with caspofungin alone (Ozcan et al 2006 ; Zeidler et al 2013 ; Keçeli et al 2014 ). Histopathological results indicated that the degree of inflammation was 25 % less in the group treated with caspofungin and meropenem than caspofungin monotherapy (Ozcan et al 2006 ).…”
Section: Antibacterial Drugsmentioning
confidence: 99%
“…The different methods of interpreting the in vitro interactions between drugs (26) and the contradictory results observed in in vitro and in vivo correlations (27)(28)(29) may contribute to the divergent results, indicating the need for standardization of the methods used to evaluate the drug interactions.…”
mentioning
confidence: 99%